Mindfulness approaches to childbirth and parenting - Hughes, A; Williams, M; Bardacke, N; Duncan, L; Dimidjian, S; Goodman, S (2009)
Mindfulness meditation Is increasingly being used as a way of managing pain, reducing stress and anxiety and, in the form of mindfulness-based cognitive therapy (MBCT), as a way of reducing the risk of recurrence in depression (NICE, 2004). This article considers its potential for parents preparing for childbirth focusing on three areas: managing pain during pregnancy and labour; reducing risk of perinatal depression; and increasing 'availability' of attention for the infant. The encouraging evidence to date suggests the possibility that mindfulness has an important contribution to make, both for reducing vulnerability in high-risk groups and as a universal intervention.